1997
DOI: 10.1590/s0100-879x1997000200014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation on the behavioral properties of crotoxin

Abstract: Crotoxin has been detoxified with gamma radiation in order to improve crotalic antiserum production. Nevertheless, present knowledge of the biological characteristics of irradiated crotoxin is insufficient to propose it as an immunizing agent. Crotoxin is known to increase the emotional state of rats and to decrease their exploratory behavior (Moreira EG, Nascimento N, Rosa GJM, Rogero JR and Vassilieff VS (1996) Brazilian Journal of Medical and Biological Research,. Therefore, we decided 1) to evaluate the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The indirect process is the main way of interaction and accounts for approximately 80 % of the total effects [ 21 , 22 ]. Previous studies showed that the most appropriate radiation dose for reducing venom toxicity and maintaining immunogenicity in order to increase the production of antiserum is 2 kGy [ 23 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…The indirect process is the main way of interaction and accounts for approximately 80 % of the total effects [ 21 , 22 ]. Previous studies showed that the most appropriate radiation dose for reducing venom toxicity and maintaining immunogenicity in order to increase the production of antiserum is 2 kGy [ 23 27 ].…”
Section: Introductionmentioning
confidence: 99%